Rhetorical actions of master’s students in the disciplinary culture of law in introduction sections - Rocha, Carlos Eduardo Mourão da; Alves, Lafity dos Santos (The ESPecialist, 2025)
Our aim here is to analyze the rhetorical organization of the Introduction section of master's dissertations of the disciplinary culture of the area of Law, with the purpose of describing how master's students in this field of study act rhetorically when producing their Introduction sections. To this end, we start from the conception that genres are communicative events with common purposes and, therefore, enable the understanding of the rhetorical actions of researchers, in the process of writing academic texts, within a discursive community (Swales, 1990; Bhatia, 2013 [1993]). A discursive community, conceived by Miller (2009) as a rhetorical community, has the power of acculturation, since members of a community tend to present apparently common values, which enables the understanding of the rhetorical organization of a genre (Swales, 1990). A community is constituted by a particular culture that represents it, which is why studies on disciplinary culture, especially those by Hyland (2004), are important to this research. Based on the analysis of the data, which began with the observation of the rhetorical organization of dissertation introductions from different postgraduate programs in Law, with a score of 6, we found that academics in the area of Law use a diverse set of rhetorical steps to write the introductions of their dissertations, which suggests that the introduction is a complex section in which several rhetorical strategies are used to achieve certain purposes. This set is composed of 10 rhetorical steps, focusing on the following aspects: objectives, research topic, methodology, theory, thematic structure, research questions, results and hypotheses.